FIRM FUNDAMENTALS AND SEASONED EQUITY OFFERING DECISION - Belau, Kazeem Seun; Ilo, Bamidele M. (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: Firms' demand for additional funds is mostly to be invested in capital demand, leverage repayment, and other related transactions. These firms, therefore, require the knowledge of firm fundamentals in order to understand factors that drive their seasoned equity issuance decision. This study examines firm fundamentals as motivations for seasoned equity offering decisions in Nigeria. Methods: The study uses data from 26 non-financial firms between 2010 and 2022 and analyzes them using descriptive and logit regression. Results: The descriptive results find that the annual average probability of seasoned equity offering is 11.53 per cent, while there is a negative capital expenditure growth rate of 2.91 per cent. The average floatation cost per share of these firms is ₦0.48k; the issue proceeds relative to the firm's market capitalization is 78.63 ratio and these firms sell shares higher than their historical price. The logit model shows that return on operating assets, cash and short-term investments, and property, plant, and equipment are negatively related, while capital demand is positively related to the seasoned equity offering decision. Conclusion and suggestion: This study concludes that firms with high operating performance, cash, and short-term investment and asset tangibility avoid seasoned equity issuance, while firms with capital demand make seasoned equity offering decisions. This study finds support for the agency theory and the demand for capital theory.